Total antioxidant activity in Quercus ilex resprouts after fire - El Omari, Bouchra; Fleck, Isabel; Aranda, Xavier; Abadía, Anunciación; Cano, Antonio; Arnao, Marino B. (Plant Physiology and Biochemistry, 2003)
After ﬁre, holm oak (Quercus ilex L.) resprouts have a higher light availability and photosynthetic activity than control plants in intact vegetation. To assess the differences in protection between these plants, we determined, in two forests, changes in gas-exchange rates, chlorophyll ﬂuorescence parameters, chloroplast pigment content and total antioxidant activity (TAA) in different seasons, at different times of the day and in relation to leaf age. The end-point method used for TAA determination allowed the evaluation of the relative contribution of hydrophilic and lipophilic antioxidants in leaf extracts. High correlations were obtained between lipophilic TAA and certain chloroplast pigment content, the highest contribution being provided by b-carotene and the components of the xanthophyll cycle (zeaxanthin + antheraxanthin, violaxanthin). All leaves showed a much higher contribution (94–99%) of hydrophilic than lipophilic antioxidants to TAA. In summer, at midday, photosynthetic rates and TAA were higher in resprouts. In these plants, reduced xanthophyll-cycle participation (as shown by non-photochemical quenching (NPQ) and xanthophyll pool content) was compensated by an increased participation of hydrophilic antioxidants. No effect of time of day or plant age was observed. The results suggest that energy dissipation as heat, and detoxiﬁcation mechanisms contribute to the protective strategies of control plants and resprouts, albeit to a different extent.
Keywords: carotenoids; non-photochemical quenching; Quercus ilex; reactive oxygen species; Resprouts; total antioxidant activity

Total antioxidant activity in Quercus ilex resprouts after fire (Plant Physiology and Biochemistry, 2003)
After ﬁre, holm oak (Quercus ilex L.) resprouts have a higher light availability and photosynthetic activity than control plants in intact vegetation. To assess the differences in protection between these plants, we determined, in two forests, changes in gas-exchange rates, chlorophyll ﬂuorescence parameters, chloroplast pigment content and total antioxidant activity (TAA) in different seasons, at different times of the day and in relation to leaf age. The end-point method used for TAA determination allowed the evaluation of the relative contribution of hydrophilic and lipophilic antioxidants in leaf extracts. High correlations were obtained between lipophilic TAA and certain chloroplast pigment content, the highest contribution being provided by b-carotene and the components of the xanthophyll cycle (zeaxanthin + antheraxanthin, violaxanthin). All leaves showed a much higher contribution (94–99%) of hydrophilic than lipophilic antioxidants to TAA. In summer, at midday, photosynthetic rates and TAA were higher in resprouts. In these plants, reduced xanthophyll-cycle participation (as shown by non-photochemical quenching (NPQ) and xanthophyll pool content) was compensated by an increased participation of hydrophilic antioxidants. No effect of time of day or plant age was observed. The results suggest that energy dissipation as heat, and detoxiﬁcation mechanisms contribute to the protective strategies of control plants and resprouts, albeit to a different extent.